Studying hospitality : beyond the envelope, papers from the 15th Annual Research Conference of the UK Council of Hospitality Management Education - Lashley, Conrad (International journal of culture, tourism and hospitality research, 2007)
An emerging hospitality studies focus among academics prioritizes the study of host and guest transactions as a key feature of hospitality research and publications. The papers in this e-book, guest edited by a leading researcher in the field, provide a flavor of some of the research themes that social science perspectives suggest. The study of host and guest transactions extends beyond commercial hospitality management activities; a large number of human interactions can be better understood through host and guest transactions. Commercial hospitality management through service quality managem.